The Implementation of PACS (Picture Archiving And Communication System) in Radiology Department of Margono Soekarjo Hospital - Asri Indah Aryani (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: This study aims to determine the evaluation and influencing factors in the implementation  of the Picture Archiving Communication System (PACS) at the Radiology Department of Margono Soekarjo Hospital, PurwokertoMethods: The type of the research is qualitative research with a purposive sampling approach which produces descriptive data in the form of pictures and written or spoken words from informants and observed behavior. Data obtained by researchers is by means of observation, in-depth interviews, and documentation. The data is analyzed using interactive model, for further drawn conclusions.Results: The results showed that PACS implemented in the radiology department of Margono Soekarjo Hospital, Purwokerto consisted of several components, namely Image Acquisition / Modality, PACS Core Application, Viewing / Reading Station. Image Acquisition / Modality. Factors that influence the implementation of the Picture Archiving Communication System (PACS) at the Radiology Department of Margono Soekarjo Hospital, Purwokerto, were manpower resources, Stability of power supply and Local Area Network, but in the implementation there was no SOP that could be used as operational guidelines for users of inpatient department, polyclinics, and emergency departments.Conclusions: Suggestions for accessing PACS can be done not only can it be accessed from a personal computer but it can be accessed from a laptop.